Association of Subclinical Hypothyroidism in Type 2 Diabetic Individuals - Noor ul ain; Sheikh Abdul Saeed; Muhammad sajid Abbas jaffri; Shazia Shakoor; Shah jabeen; Sana Kashif (Pakistan Journal of Medical Research)
Background: Diabetes Mellitus and Thyroid Disorders, both ranks as most prevalent endocrine diseases in clinical practice for last several years. Thyroid hormones play a pivotal role in various metabolic pathways, including carbohydrate metabolism.